Them : why we hate each other-- and how to heal - Sasse, Benjamin E. (St. Martin's Press, 2018)
Presents an assessment of the existential crisis in modern America that explores how increasing social isolation and the collapse of traditional community connections lead to tension and pessimism, arguing that the solution is a rediscovery of human connections.